Between Work and Study: Psikoedukasi Manajemen Stres pada Mahasiswa Pekerja - Indah Fitriani; Djudiyah Djudiyah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Working students face academic and work demands simultaneously, making them vulnerable to stress and difficulties in managing it. Stress management psychoeducation is expected to help working students understand the concept of stress, coping strategies, and assertive communication as skills that support interpersonal stress management. This study aims to evaluate changes in the cognitive understanding of working students after participating in group-based stress management psychoeducation activities. The study used a one-group pretest–posttest design with six working students participating in a public speaking training community. The program was implemented through structured sessions using lectures, worksheets, case studies, focused group discussions, relaxation role plays, and priority setting exercises. Understanding was measured using a multiple-choice test with four alternative answers. The analysis results showed t = −7.05 with p = 0.001 (p < 0.05). This indicates that stress management psychoeducation has a significant effect on working students. The post-test mean (M=7.50) was greater than the pre-test mean (M = 5.33). These findings indicate that stress management psychoeducation was followed by an increase in working students' cognitive understanding of stress, coping, and assertive communication skills relevant to the context of dual roles.